Real-World Outcomes of Ruxolitinib as Salvage Therapy in Steroid-Refractory Acute and Chronic Graft-Versus-Host Disease: A Multicenter Retrospective Observational Study from Turkey - Bakirtas, Mehmet; Berber, Ilhami; Hindilerden, Ipek Yonal; Dal, Mehmet Sinan; Izmir Guner, Sebnem; Uysal, Ayse; Altuntas, Fevzi (Mdpi, 2026)
Introduction & Objective: Graft-versus-host disease (GVHD) is a major complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT), with limited treatment options for steroid-resistant cases. Ruxolitinib, a JAK1/2 inhibitor, has shown promise in treating steroid-resistant acute (aGVHD), chronic (cGVHD), and overlap GVHD (oGVHD), but real-world data remain limited. This study evaluated the real-world efficacy and safety of ruxolitinib in allo-HSCT patients with steroid-resistant GVHD. Materials & Methods: This retrospective, multicenter study included adult patients treated with ruxolitinib for Grade II or higher aGVHD or moderate-to-severe cGVHD at nine centers in Turkey (2017-2024). Clinical characteristics, treatment responses, and adverse events were recorded. Primary outcomes were overall response rate (ORR) and overall survival (OS). Results: Among 80 patients (mean age: 39.3 +/- 13.3 years; 60 males), 39 had aGVHD, 68 cGVHD, and 15 oGVHD. The ORR was 72 of 80 patients (90.0%) (complete response: 37 of 80 [46.3%], partial response: 35 of 80 [43.8%]). The 1-year and 2-year OS rates were 91.3% and 82.5%. Severe cGVHD (p < 0.001) and lack of response to ruxolitinib (p = 0.018) were associated with reduced OS. Adverse events included infections in 40 of 80 patients (50.0%), cytopenias in 23 of 80 (28.7%), and cytomegalovirus reactivation in 20 of 80 (25.0%). Conclusion: In this retrospective multicenter cohort, ruxolitinib was associated with high response rates in steroid-refractory GVHD, while disease severity remained a key determinant of survival, and findings should be interpreted as exploratory.
Keywords: hematopoietic stem cell transplantation; graft-versus-host disease; Janus Kinase Inhibitor; ruxolitinib; survival analysis; Adverse Drug Event